Analisis Penerapan Alat Peraga Sederhana Pada Keluarga Anak Usia Sekolah Dengan Masalah Kesehatan Gigi Di Desa Tongkaina Kecamatan Bunaken - Witni Alicia Santi; Septriani Renteng; Toar, Juwita (Mapalus Nursing Science Journal, 2025)
Background: Background: Tooth decay is one of the health problems for children. One of the dental decays experienced by children occurs due to parents' lack of knowledge about children's dental and oral health. Oral health that is not paid attention to will have an impact on the development of children's overall abilities, both physical and intellectual. Health education is one of the effective ways for school-age children because it is an age group that is sensitive and easily receptive to change and is a very important domain to influence a person's behavior, so that the higher or more knowledge a person gets, the better the behavior shown by the person. Objective: To present the results of practice in the form of nursing care in families with the developmental stage of school-age children with a health education and demonstration approach. Methods: Case study, with health education methods, guessing games, audiovisual, making miniature teeth and mouth, brushing demonstrations. Results: After providing health education interventions, guessing games, audiovisuals, making miniature teeth and mouth, and toothbrush demonstrations were effective in increasing family knowledge about the developmental stages of families of school-age children. Conclusion: The provision of health education interventions, play therapy and demonstrations is useful in adding insight and knowledge to families to maintain dental and oral health.